2020
DOI: 10.1007/s00540-020-02858-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and associated risk factors for limb amputation among sepsis survivors in South Korea

Abstract: Purpose Peripheral gangrene (PG) is a known complication requiring limb amputation among sepsis survivors; however, its incidence and associated risk factors remain controversial. We aimed to examine the incidence of limb amputation among sepsis survivors, and to investigate factors independently associated with limb amputation. Methods In this population-based cohort study, data obtained from the South Korean national health insurance service database between 2015 and 2016 were analyzed. A sepsis survivor was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…based cohort study in South Korea concluded that 0.8% of sepsis survivors underwent limb amputation to treat peripheral gangrene. They also found that sepsis survivors with chronic pre-morbid conditions such as diabetes mellitus and peripheral arterial disease or those who received specific vasopressor treatments (epinephrine and dopamine) were more likely to undergo limb amputation [8].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…based cohort study in South Korea concluded that 0.8% of sepsis survivors underwent limb amputation to treat peripheral gangrene. They also found that sepsis survivors with chronic pre-morbid conditions such as diabetes mellitus and peripheral arterial disease or those who received specific vasopressor treatments (epinephrine and dopamine) were more likely to undergo limb amputation [8].…”
Section: Discussionmentioning
confidence: 97%
“…However, restoring multiple limbs amputation bears a higher level of challenges toward successfully recovering the functional capacities. Figure 4 According to the World Health Organization, 0.5% of the population in a developing country has some degree of physical disabilities that require rehabilitation services and the need for prosthesis or orthosis to support their daily activities 8 . WHO survey analysis demonstrated that people with disabilities were more than twice as likely to seek healthcare expertise due to inadequate equipment…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have reported a 0.8% to 2.2% rate of extremity amputation in survivors of sepsis, most commonly of the lower extremities. 6,7 Unlike trauma patients with isolated limb injuries, patients with amputations as a complication of sepsis have survived through a state of global tissue hypoperfusion and multisystem organ failure with effects on the entire body’s physiology. Consequently, prosthetic rehabilitation can be particularly challenging for these patients.…”
Section: Introductionmentioning
confidence: 99%